Efficiency of Some Insecticides in Controlling Citrus Leafminer, Phyllocnistis citrella Stainton (Lepidoptera: Gracillariidae) - Faskha, Shadi (ENTOMOLOGIA HELLENICA, 2022)
The toxicity of four commercial insecticides (mineral oil, azadirachtin, phenthoate and abamectin) in addition to mint oil (variety of terpenoids), against the citrus leaf-miner, Phyllocnistis citrella, larvae, was tested under laboratory conditions using the leaf-dipping method. The bioassay data indicated that abamectin was the most toxic insecticide against P. citrella larvae, followed by azadirachtin, phenthoate, mint oil and finally mineral oil. On the other hand, field evaluation showed that the highest larval mortality was 94.79 and 83.87% induced by abamectin and azadirachtin, respectively, five days after the 2nd application. Mineral oil and phenthoate showed a 72.43 and 61.4% mortality respectively, at 11 days after the 2nd application, and finally mint oil, 49.82% three days after the 1st application.